TRAINING AND MENTORING FOR ONLINE-BASED TRANSACTION RECORDING (ONLINE TRANSACTION PROCESSING SYSTEMS-OLTP) - Alamsyah, Muhammad Iqbal; Kosadi, Ferry; Ridwan (Pasundan International of Community Services Journal (PICS-J), 2023)
Virageawie is a company that consists of bamboo craftsmen. We see that there is a need for support for increasing partner empowerment, especially in improving partner management capabilities. The problem is, in its activities/operations the use of digital media for transactions made has not provided convenience and speed in the process of transactional reporting and financial reports. There are obstacles including technical capabilities in the use of information technology, the process of correction and reconciliation of data received from each provider, and conversion to a format that is following the habits of business actors, besides that in terms of understanding the procedures and processes for preparing financial reports by Accounting Standards Finance (SAK). The solution that will be provided is in the form of establishing a transaction recording system and preparing digital-based financial reports, training regarding the use of digital-based transaction recording and financial reporting tools, and assistance/assistance for 3 months until partner HR can be completely released and able to run the new system. Material/content related to formation, training, and mentoring is based on the results of previous research from service members, which had been carried out previously at the binongjati knitting center in Bandung City. The output target in this Community Service is that the partner's management ability (virageawie) increases, with evidence of a description of the results of the management ability test/score before and after the activity.